Chronic bronchitis in coal miners: ante-mortem/post-mortem comparisons. Issue 5 (September 1969) - McKenzie, H. I.; Glick, M.; Outhred, K. G.
Abstract : From bronchial measurements in 136 deceased coal miners a comparison with well-documented ante-mortem findings shows that with increasing clinical severity of chronic bronchitis there is increasing narrowing of intrapulmonary airways due to wall thickening at the expense of the lumen. With the aid of the Reid index (gland/wall ratio) and a new proposed index which more directly measures airway obstruction—the wall internal to cartilage/lumen radius ratio—both of which tend to be independent of bronchus size but change with increasing abnormality—it is possible to quantitate chronic bronchitis pathologically and to obtain satisfactory correlations with ante-mortem data. Chronic bronchitis may thereby be evaluated independently from pneumoconiosis and emphysema, thus facilitating the study of their separate relationships with cigarette smoking and with other possible aetiological factors.